Receptor tyrosine kinases and schistosome reproduction: new targets for chemotherapy - Morel, Marion; Vanderstraete, Mathieu; Hahnel, Steffen; Grevelding, Christoph G.; Dissous, Colette (Frontiers in Genetics, 2014)
Schistosome parasites still represent a serious public health concern and a major economic problem in developing countries. Pathology of schistosomiasis is mainly due to massive egg production by these parasites and to inflammatory responses raised against the eggs which are trapped in host tissues. Tyrosine kinases (TKs) are key molecules that control cell differentiation and proliferation and they already represent important targets in cancer therapy. During recent years, it has been shown that receptor tyrosine kinases (RTK) signaling was active in reproductive organs and that it could regulate sexual maturation of schistosomes and egg production. This opens interesting perspectives for the control of transmission and pathogenesis of schistosomiasis based on new therapies targeting schistosome RTKs. This review relates the numerous data showing the major roles of kinase signaling in schistosome reproduction. It describes the conserved and particular features of schistosome RTKs, their implication in gametogenesis and reproduction processes and summarizes recent works indicating that RTKs and their signaling partners are interesting chemotherapeutical targets in new programs of control.